Determinants of Rural Women Involvement in Farming Activities in Akwa Ibom State, Nigeria - Akaninyene, Obot; Rachael, Obed; Ngozi, Obiewke (Canadian Journal of Agriculture and Crops, 2022)
The study was conducted to examine the involvement of rural women in farming activities in Akwa Ibom State, Nigeria. The specific objectives were to examine the socio-economic characteristics of the respondents; identify the farming activities involved in and the constraints to women involvement in farming activities. Primary data was used for the study. The primary data were obtained with the aid of structured questionnaires administered to 175 rural women who were randomly selected. Frequency and percentage were used to analyze the objectives (1, 2 and 3) while multiple regression was used to test the relationship between the socio-economics characteristics and the involvement of women in farming activities. The result indicated that rural women were more into planting (39.9%), weeding (36.0%) and harvesting (14.9%) than other farming activities in the study area. On the constraints, the rural women identified lack of finance and poor returns (profit) as hinderance to women active involvement in full time farming activities. Also, the result from the regression analysis at 1% and 5% confidence interval revealed that age, marital status, household size and farm size were positively related to influencing rural women active involvement in farming activities. The study therefore recommended that government and non-governmental organization focus more in empowering rural women to access institutional credit and also build their capacity on the use of modern technology in planting, weeding and harvesting.